A waste biomass-derived photothermic material with high salt-resistance for efficient solar evaporation. (March 2022) - Guan, Heng-Shu; Fan, Ting-Ting; Bai, Hao-Yan; Su, Ying; Liu, Zhong; Ning, Xin; Yu, Miao; Ramakrishna, Seeram; Long, Yun-Ze
Abstract: Effective use of solar energy to produce steam for solving the problem of global shortage of fresh water is considered to be a promising technology. In this work, we reported a low-cost, high-efficient, waste biomass-derived solar evaporator with Janus structure was readily constructed from porous pomelo peel (PP). This multifunctional photothermal sponge has a hydrophobic top layer and a hydrophilic bottom layer to prevent the accumulation of salt on the surface of the evaporator, ensuring high efficiency and stable water vapor output. After hydrophobic modification of one side of freeze-dried PP, MXene was sprayed on the Janus PP (JPP), the interfacial solar energy driven water evaporation can be effectively realized for seawater desalination. The evaporation rate and solar thermal conversion efficiency of JPP@MXene (JPP@M) under simulated sunlight irradiation with one sun (1 kW m −2 ) were 1.48 kg m −2 ·h −1 and 92.3% respectively. Under simulated sunlight irradiation of 1 sun, a high efficiency evaporation performance could be maintained after 50 cycles. In addition, JPP@M could be used to effectively reduce the viscosity of heavy crude oil through solar-assisted heating, resulting in effective purification. Moreover, JPP@M exhibited excellent antibacterial property, which is more important for biomass samples. This cost-efficient, sustainable and eco-friendly photothermic sponge is expected to be used for large-scale wastewater treatment and clean water generation. Graphical abstract: Image 1 Highlights: JPP@MXene exhibited excellent water evaporation rate and efficiency. JPP@MXene had a hydrophobic top layer and a hydrophilic bottom layer to prevent surface salt deposition. JPP@MXene showed excellent efficiency in reducing the viscosity of heavy oil with auxiliary heating. JPP@MXene possessed excellent bactericidal performance and cycle performance.